A Union Member's Perspective on Technological Change - Cunningham, Bart; Hull, Dennis (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1988)
After having defined some of concerns union members have with technological change, this paper outlines the recent history of such changes in the telecommunications industry before offering a viewpoint on future responses to the issue.